Point-of-care ultrasound of peripheral nerves in the diagnosis of Hansen's disease neuropathy - Voltan, Glauber; Filho, Fred Bernards; Leite, Marcel Nani; De Paula, Natália Aparecida; Santana, Jaci Maria; Silva, Claudia Maria Lincoln; Barreto, Josafá Gonçalves; Da Silva, Moises Batista; Conde, Guilherme; Salgado, Claudio Guedes; Frade, Marco Andrey Cipriani (Frontiers in Medicine, 2022)
Introduction Hansen's disease (HD) is the most common cause of treatable peripheral neuropathy in the world that may or may not involve skin manifestations, and physical examination based on simplified neurologic evaluation is a subjective and inaccurate procedure. High-resolution ultrasound (HRUS) can be used to evaluate peripheral nerves and is a validated technique of good reproducibility, permitting a detailed and precise examination. Objectives We proposed to establish objective criteria for absolute values of the measurement of the CSA of peripheral nerves and their indices of the ΔCSA and ΔTpT in the diagnosis of Hansen's disease neuropathy as compared with healthy voluntaries. Materials and methods In municipalities from different regions of Brazil, we randomly selected 234 volunteer Brazilian patients diagnosed with leprosy to be submitted to peripheral nerve echography and compared with 49 healthy Brazilian volunteers. Results Hansen Disease assessed by high resolution ultrasound is a primarily neural disease that leads to multiple hypertrophic mononeuropathy characterized by CSA values exceeding normal limits (Med CT = 10.2 mm2; UT = 9.8 mm2; UPT = 9.3 mm2; CFFH = 18.3 mm2; T = 9.6 mm2), and the pattern of asymmetry (ΔCSA>2.5 mm2 with RR 13) and focality (ΔTPT > 2.5 mm2 with RR 6.4) of this thickening has higher sensitivity (76,1%) and specificity (87,8 %) for its early diagnosis that laboratory tests. Analyzing each subject, the percentage of thickened nerves detected among the total number of nerves assessed was higher among patients with HD than among healthy individuals (p < 0.0001). Individuals with two or more thickened nerves were at 24.1 times higher relative risk (95% CI: 6.74–88.98) of HD.